Analysis of Mechanisms for Increased Blood Pressure Variability in Rats Continuously Infused with Angiotensin II. (4th January 2023) - Jiang, Danfeng; Matsuzaki, Minami; Kawagoe, Yukiko; Kitamura, Kazuo; Tsuruda, Toshihiro; Kaikita, Koichi; Asada, Yujiro; Kato, Johji
Abstract : Objective . We reported that rats infused with angiotensin II (Ang II) are not only a model of hypertension but also of augmented 24 h blood pressure variability (BPV). In this study, we examined the mechanisms for Ang II-induced BPV, focusing on BP, heart rate (HR), baroreceptor reflex sensitivity (BRS), and medial area of the aortic arch. Methods . Nine-week-old male Wistar rats were infused with subcutaneous 5.2 μ g/kg/h Ang II with or without oral administration with 30 mg/kg/day azelnidipine for 14 days. BP and HR were recorded every 15 min under an unrestrained condition by a radiotelemetry system, while BPV was evaluated by standard deviation of BP. BRS was quantified by a sequence analysis, and medial thickness of the aortic arch was measured by microscopic examination. Results . BPV increased at days 7 and 14 following continuous infusion of Ang II. Before the infusion, a positive correlation was found between BP and HR, but it became negative at day 7 and then weakened or disappeared at day 14. BRS was slightly impaired at day 7 and significantly lowered at day 14, a phenomenon accompanied by thickened medial area of the aortic arch in Ang II-infused rats. Those Ang II-induced alterations were all significantly attenuated by azelnidipine. Conclusions . The present findings suggest sequential changes in the mechanisms behind augmented BPV in rats continuously infused with Ang II over 14 days.